Patterns of Focal Gray Matter Atrophy Are Associated With Bradykinesia and Gait Disturbances in Older Adults - Rosano, Caterina (Oxford University Press, 2012)
OBJECTIVES. Identify the neuroimaging correlates of parkinsonian signs in older adults living in the community. METHODS. Magnetic resonance imaging was obtained in 307 adults (82.9 years, 55% women, 39% blacks) concurrently with the Unified Parkinson Disease Rating scale—motor part. Magnetic resonance imaging measures included volume of whole-brain white matter hyperintensities and of gray matter for primary sensorimotor, supplementary motor, medial temporal areas, cerebellum, prefronto-parietal cortex, and basal ganglia. RESULTS. About 25% of the participants had bradykinesia, 26% had gait disturbances, and 12% had tremor. Compared with those without, adults with any one of these signs were older, walked more slowly, had worse scores on tests of cognition, mood and processing speed, and higher white matter hyperintensities volume (all p ≤ .002). Gray matter volume of primary sensorimotor area was associated with bradykinesia (standardized odds ratio [95% confidence interval]: 0.46 [0.31, 0.68], p < .0001), and gray matter volume of medial temporal area was associated with gait disturbances (0.56 [0.42, 0.83], p < .0001), independent of white matter hyperintensities volume and age. Further adjustment for measures of muscle strength, cardiovascular health factors, cognition, processing speed, and mood or for gait speed did not substantially change these results. CONCLUSIONS. Atrophy within primary sensorimotor and medial temporal areas might be important for development of bradykinesia and of gait disturbances in community-dwelling elderly adults. The pathways underlying these associations may not include changes in white matter hyperintensities volume, cognition, information processing speed, mood, or gait speed.